The Colombian peace deal and its impact on the evolution of tropical diseases agents (2018)
The armed conflict in Colombia (FARC rebels vs. Colombian government) is one of the oldest in Western countries, including thousands of deaths, massacres and terrible living conditions for those who have perceived it closely. It was until 2016 that this conflict reached a historic and longed for ceasefire agreement. This new social condition brought many benefits for the country, since agriculture has been renewed and trade and tourism have been activated in many regions that were affected by this senseless war. However, it should be noted that this reintegration and migration of individuals outside the law, and even of the same military of the National Army that were in combat, involved in wild cycles of insects and pathogens transmitting diseases to rural areas where mosquitoes also circulate; can have an impact on National Health Systems and plans for the control and prevention of vector-borne diseases, as they could cause outbreaks where infection rates are increased mainly in the normalization zones (“zonas veredales”) where FARC numbers will be concentrated. This may have an effect on the diversity of causal agents of these diseases. Then, it would be of great importance to have an adequate management plan and to keep in mind the costs that must be assumed by the government for the diagnosis, treatment and surveillance of people who may be affected. © 2017 Elsevier B.V.